Synthesis and Reactivity of α-Diazo-β-keto Sulfonamides - Judge, Evan R.; O’Shaughnessy, Keith; Lawrence, Simon E.; Collins, Stuart G.; Maguire, Anita R. (Synthesis, 2024)
Copper-mediated reactions of α-diazo-β-keto sulfonamides led to a range of products, including alkynesulfonamides, enamines, and α-halosulfonamides, with no evidence for intramolecular C–H insertion in any of the reactions, in contrast to the reactivity of the comparable α-diazo-β-oxo sulfones. Use of copper(II) triflate (5 mol%) led to the isolation of a series of alkynesulfonamides (up to 12% yield) and enamines (up to 64% yield). Use of copper(II) chloride (5 mol%) led to the formation, in addition, of α-halosulfonamides; use of stoichiometric amounts of copper(II) chloride/bromide enabled facile halogenation of the β-keto sulfonamide to form α-halosulfonamides (up to 63% yield).
Keywords: C–H insertion; diazo compounds; copper catalysis; alkynesulfonamides; α-halosulfonamides